2015
DOI: 10.5713/ajas.14.0761
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular Uptake and Cytotoxicity of β-Lactoglobulin Nanoparticles: The Effects of Particle Size and Surface Charge

Abstract: It is necessary to understand the cellular uptake and cytotoxicity of food-grade delivery systems, such as β-lactoglobulin (β-lg) nanoparticles, for the application of bioactive compounds to functional foods. The objectives of this study were to investigate the relationships between the physicochemical properties of β-lg nanoparticles, such as particle size and zeta-potential value, and their cellular uptakes and cytotoxicity in Caco-2 cells. Physicochemical properties of β-lg nanoparticles were evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…As the chitosan coated (M2 and R2) formulations (22.6 ± 0.34 mV, 23.7 ± 0.03mV) have more zeta potential than uncoated (M1 and R1) formulations (-7.68 ± 0.02 mV, -6.51 ± 0.03 mV) so the % inhibition of the A549 and H1299 cells was found more in these formulations. Higher value of positive zeta potential facilitates cytotoxicity in cancer cells due to stronger interaction with tumor cell membrane 28,29 . He et al, found that an increase in zeta-potential values of carboxymethyl chitosan grafted methyl methacrylate nanoparticles resulted in a significant rise in the cellular uptake of nanoparticles in murine macrophage cells 29 .…”
Section: Fig 3: Overlay Of Ftir Spectras Of (A) Soya Lecithin (B) Fomentioning
confidence: 99%
See 2 more Smart Citations
“…As the chitosan coated (M2 and R2) formulations (22.6 ± 0.34 mV, 23.7 ± 0.03mV) have more zeta potential than uncoated (M1 and R1) formulations (-7.68 ± 0.02 mV, -6.51 ± 0.03 mV) so the % inhibition of the A549 and H1299 cells was found more in these formulations. Higher value of positive zeta potential facilitates cytotoxicity in cancer cells due to stronger interaction with tumor cell membrane 28,29 . He et al, found that an increase in zeta-potential values of carboxymethyl chitosan grafted methyl methacrylate nanoparticles resulted in a significant rise in the cellular uptake of nanoparticles in murine macrophage cells 29 .…”
Section: Fig 3: Overlay Of Ftir Spectras Of (A) Soya Lecithin (B) Fomentioning
confidence: 99%
“…The particle size of chitosan coated nanoliposomes appeared to be the controlling factor affecting the cytotoxicity of the batch M2. A decrease in the size of nanoliposomes may lead to an increase in the interactions and binding with cell membranes, which can result in enhanced cytotoxicity of chitosan coated nanoliposomes 28,30,31 . Zhang et al, reported that drug uptake in cancer cells reliant on the particle size.…”
Section: Fig 3: Overlay Of Ftir Spectras Of (A) Soya Lecithin (B) Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle cell interactions can be remarkably different from that of small or large sized particles at nanoscale [24]. As nanoparticles with a smaller size have larger surface areas available to adhere and interact with cell membranes, the decrease of nanoparticle size may lead to an increase in mobility and interaction with cell membranes, which can result in enhanced cellular uptake of nanoparticles [25]. Besides, because of their small size, nanoparticles are often not recognized as a foreign agent by macrophages and consequently do not enter macrophages through membrane pores to be led to the digestion apparatus for such microparticles, the reticuloendothelial system [26].…”
Section: Physical Properties and Applications Of Nanoparticle Based Dmentioning
confidence: 99%
“…8 There are lots of different kinds of protein nanoparticles reported, such as bovine serum albumin, 9,10 casein, 11,12 collagen, 13 b-lacto globulin 14,15 and other animal proteins. 16 However, reports about the application of plant protein in the preparation of nanoparticles as the matrix material are relatively few.…”
Section: -4mentioning
confidence: 99%